Investigating the inoculum dynamics of Cladosporium on the surface of raspberry fruits and in the air - Farwell, Lauren Helen; Papp-Rupar, Matevz; Deakin, Greg; Magan, Naresh; Xu, Xiangming (Wiley, 2024)
Raspberry production is under threat from the emerging fungal pathogenic genus Cladosporium. We used amplicon-sequencing, coupled with qPCR, to investigate how fruit age, fruit location within a polytunnel, polytunnel location and sampling date affected the fruit epiphytic microbiome. Fruit age was the most important factor impacting the fungal microbiome, followed by sampling date and polytunnel location. In contrast, polytunnel location and fruit age were important factors impacting the bacterial microbiome composition, followed by the sampling date. The within-tunnel location had a small significant effect on the fungal microbiome and no effect on the bacterial microbiome. As fruit ripened, fungal diversity increased and the bacterial diversity decreased. Cladosporium was the most abundant fungus of the fruit epiphytic microbiome, accounting for nearly 44% of all fungal sequences. Rotorod air samplers were used to study how the concentration of airborne Cladosporium inoculum (quantified by qPCR) varied between location (inside and outside the polytunnel) and time (daytime vs. nighttime). Quantified Cladosporium DNA was significantly higher during the day than the night and inside the polytunnel than the outside. This study demonstrated the dynamic nature of epiphytic raspberry fruit microbiomes and airborne Cladosporium inoculum within polytunnels, which will impact disease risks on raspberry fruit.